Can MRI be used as a safe and expedient option for calculating Spinal Instability Neoplastic Score for patients with metastatic spinal cord compression?. (1st May 2021) - Hurley, Patrick; Azzopardi, Christine; Botchu, Rajesh; Grainger, Melvin; Gardner, Adrian
Abstract : Aims: The aim of this study was to assess the reliability of using MRI scans to calculate the Spinal Instability Neoplastic Score (SINS) in patients with metastatic spinal cord compression (MSCC). Methods: A total of 100 patients were retrospectively included in the study. The SINS score was calculated from each patient's MRI and CT scans by two consultant musculoskeletal radiologists (reviewers 1 and 2) and one consultant spinal surgeon (reviewer 3). In order to avoid potential bias in the assessment, MRI scans were reviewed first. Bland-Altman analysis was used to identify the limits of agreement between the SINS scores from the MRI and CT scans for the three reviewers. Results: The limit of agreement between the SINS score from the MRI and CT scans for the reviewers was -0.11 for reviewer 1 (95% CI 0.82 to -1.04), -0.12 for reviewer 2 (95% CI 1.24 to -1.48), and -0.37 for reviewer 3 (95% CI 2.35 to -3.09). The use of MRI tended to increase the score when compared with that using the CT scan. No patient having their score calculated from MRI scans would have been classified as stable rather than intermediate or unstable when calculated from CT scans, potentially leading to suboptimal care. Conclusion: We found that MRI scans can be used to calculate the SINS score reliably, compared with the score from CT scans. The main difference between the scores derived from MRI and CT was in defining the type of bony lesion. This could be made easier by knowing the site of the primary tumour when calculating the score, or by using inverted T1-volumetric interpolated breath-hold examination MRI to assess the bone more reliably, similar to using CT. Cite this article: Bone Joint J 2021;103-B(5):971–975.